Intracerebral Implantation of Hydrogel-Coupled Adhesion Peptides: Tissue Reaction. (1995) - Woerly, S.; Laroche, G.; Marchand, R.; Pato, J.; Subr, V.; Ulbrich, K.
Abstract : Arg-Gly-Asp peptides (RGD) were synthesized and chemically coupled to the bulk of N-(2-hydroxypropyl) methacrylamide-based polymer hydrogels. Fourier Transform Infrared Spectroscopy (FFIR) and amino acid analysis confirmed the peptide coupling to the polymer. Activated and control (unmodified) polymer matrices were stereotaxically implanted in the striata of rat brains, and two months later the brains were processed for immunohistochemistry using antibodies for glial acidic fibrillary protein (GFAP), laminin and neurofilaments. RGD-containing polymer matrices promoted stronger adhesion to the host tissue than the unmodified polymer matrices. In addition, the RGD-grafted polymer implants promoted and supported the growth and spread of GFAP-positive glial tissue onto and into the hydrogels. Neurofilament-positive fibers were also seen running along the surface of the polymer and, in some instances, penetrating the matrix. These findings are discussed in the context of using bioactive polymers as a new approach for promoting tissue repair and axonal regeneration of damaged structures of the central nervous system.